THE LEVEL OF ENVIRONMENTAL COMFORT OF URBAN FOREST AREA BASED ON THE CHARACTERISTICS OF URBAN FOREST IN KISARAN CITY - Dewi Sri Amela Nainggolan; Defri Yoza; Rudianda Sulaeman (Jurnal Ilmu Ilmu Kehutanan, 2017)
Negative impacts due to development that are not environmentally friendly in urban area need to be reduced through the provision of green open-space. One of the green open-space in urban high aesthetic value and which can be used as a means of recreation is the urban forest. Urban forest that has the composition or richness of floristic tropical forests as well as the relatively large densities associated with environmental conditions such as climate, soil and light. Comformity level in Kisaran City is currently in the range uncomfortable category (HI value = >26). The management of urban forest that still prioritize aesthetic functions rather than hydrological functions has a role in determining the sense of comfort for people around the city forest